Vozes de mulheres na literatura brasileira contemporânea : feminismos diversos, romance singular - As meninas, de Lygia Fagundes Telles - Tuschinski, Josélia de Fátima (2023)
This work studies the echoes of the Feminisms present in the voices of the protagonists, Lorena, Lia and Ana Clara, in the contemporary novel As Meninas, by Lygia Fagundes Telles, published in 1973 In the path of literary studies focused on the history of fictional women’s writing, in dialogue the social history of women, the legitimacy of feminism as an important component of the work piece As meninas, in order to enable the debate on gender issues, taking into account the political character of examining and contesting the power relationships that interfere with sexuality and the reproductive right of the protagonists. The analyses are anchored in literary studies, gender studies, philosophical and sociological studies that dialogue with the issue of women. The choice of these approaches is justified by the need to establish interlocutions with different areas of knowledge that deal with the issue of the woman’s voice in life and art. Thus, the theoretical basis of this dissertation is based especially on the studies of Mary Del Priore (2013, 2020). Heleieth Saffioti (2013, 2015), Rose Marie Muraro (1983), Marcia Tiburi (2021), Flávia Biroli and Luís Felipe Miguel (2014), Michel Foucault (2021) and Mikhail Bakhtin (2015). As for the methodological procedures, this corresponds to research of an applied nature, exploratory as its objectives, bibliographical as its technical procedures and qualitative as its approach. As a result, it is possible to perceive that the novel As meninas, through the heterodiscus possesses, as a guiding thread, the voices of the narrators’ characters, their subjectivities, fears and conflicts. In the case of the relationship between feminism literature, in addition to the transgressor discourse that composes the voices of the protagonists, there is also an interlocution on the structural level of the work, which ends up establishing a literature-culture-society relationship.